To change or not to change: does it affect my school? - Padzil, Iskandar; Abdul Kadir, Suhaida; Mohd Ayub, Ahmad Fauzi; Arshad, Mohd Mursyid (Human Resource Management Academic Research Society, 2021)
An effective education system needs to be developed and changed to meet current and future claims. As such, in the face of today’s challenging global economic challenge, citizens with knowledge, skills and competencies are crucial to the country’s success, based on high-performance education. This study aims to determine the predictors of school effectiveness in secondary schools based on the perception of the principals. Data was collected from 246 principals in low-performance schools using the survey questionnaire. The selection of the respondents based on proportionate stratified random sampling. The Structural Equation Modelling analysis showed that the model tested and evaluated was fit. Based on four constructs, namely the appropriateness of change, management support, change of efficacy and personal valence, the variance explained for school effectiveness is approximately 26.3%. The findings indicated that the appropriateness of change and support for management were the main predictors of school effectiveness. The study concluded that the appropriateness of change and management support plays a vital role in the efficiency of schools among principals in low-performance schools. Changes in educational settings need to be adapted to school development to ensure that the school communities successfully adapt changes.